Exploring natural variation for rice sheath blight resistance in Brachypodium distachyon. (2nd January 2019) - Gill, Upinder S.; Lee, Seonghee; Jia, Yulin; Mysore, Kirankumar S.
ABSTRACT: Sheath blight caused by the soil borne fungus Rhizoctonia solani AG1-IA is one of the major diseases of rice in the world. Genetic resistance in rice against this disease has not been very successful. Brachypodium distachyon is considered as a model species for several cereal crops and it has been studied in the past to identify novel sources of disease resistance against cereal crop diseases. Therefore, the current study was designed to explore nonhost disease resistance in Brachypodium accessions against sheath blight pathogen of rice, Rhizoctonia solani . A total of 19 Brachypodium distachyon accessions were screened for resistance against Rhizoctonia solani AG1-IA. Different levels of resistance reactions were observed among accessions. Quantification of jasmonic acid (JA) and salicylic acid (SA) concentration in selected resistant (Bd3-1), moderately susceptible (Bd21), and susceptible (Bd30-1) inbred accessions revealed that Bd3-1 accumulated more JA upon pathogen infection compared to Bd21 or Bd30-1. In contrary, no differences were observed for SA accumulation in tested accessions suggesting that the resistance to R. solani in Brachypodium is due to an SA-independent defense pathway. Our study provides a new foundation to explore this area for more durable resistance against this disease.